Driving Mechanism of Comprehensive Land Consolidation on Urban–Rural Development Elements Integration - Yuyao Zuo; Chaoxian Yang; Guixin Xin; Ya Wu; Rongrong Chen (Land, 2023)
Identifying the driving mechanism of comprehensive land consolidation (CLC) on urban–rural development elements integration (URDEI) is of great significance for promoting the coordinated development of urban and rural areas. Based on the composition of urban and rural element systems, this study establishes the theoretical framework of the influence of CLC on URDEI and verifies the framework through empirical cases in Chongqing, China. The results show that (1) CLC promotes URDEI and realizes the rational allocation of urban and rural resources by improving the quality of urban and rural elements and opening up two-way flow channels. (2) The case analysis demonstrates that CLC can improve the quality of rural elements and increase the added value of the flow to the city, which in turn drives urban elements such as talents, technology, and capital to pour into the countryside, therefore forming a realistic path for the URDEI. This study helps understand the role of CLC in the transformation of URDEI and provides a reference for the scientific implementation of land consolidation.